Effectiveness of Talking Stick Learning Model in Improving the Mastery of Arabic Vocabulary at Madrasah Tsanawiyah Darussalam Samarinda - Lala Nur Hasanah; Muhammad Ihsanuddin Masdar (Al-Jawhar : Journal of Arabic Language, 2024)
Mufrodat is one of the language elements that must be mastered. However, the problem that students often face when learning a foreign language, including Arabic, is that students easily forget in remembering a number of vocabulary that has been memorized. To overcome this problem, the researcher offers a Talking Stick learning model to improve the mastery of Arabic vocabulary. This study aims to determine the effectiveness of the Talking Stick learning model in improving students' mastery of Arabic vocabulary. This research is a quantitative research with a type of quasi experiment approach (pseudo experiment) design the non-equivalent control group, with a sample of 27 students consisting of 14 students (control class) and 13 students (experimental class). The data collection method used was a test consisting of pre-test and post-test. The data analysis technique used was the independent sample t-test. Based on the research results obtained, the average value of the post-test in the experimental class was 90, while the control class was 60. The results of data analysis using the independent sample t-test showed that the significance value (2 tailed) was 0.000 <0.05. It can be said that  is rejected and  is accepted. Based on the results of the N-Gain Score calculation, it shows that the average value of the N-Gain score for the experimental class is 0.7840, including in the high category. So it can be concluded that the Talking Stick learning model is effective in a high category in improving students' mastery of Arabic vocabulary at Madrasah Tsanawiyah Darussalam Samarinda.